The relationship between the xenotransplantation limitations and Charles Darwin theory on human evolution - Condello, Ignazio; Condello, Salvatore (Acta Biomedica Atenei Parmensis, 2020)
The need for an alternative source of donor organs, together with the expansion of scientific data in this field, has focused attention on xenotransplantation as a possible alternative to allotransplantation in the treatment of patients with end-stage disease of vital organs. The fundamental property called ‘evolution’ was not discovered in the study of living matter by Darwin, but in the study of the foundations of the Logic of Nature, i.e. in first level Galilean Science. The work of Darwin was aiming at the discovery of the origin of the human species and the property of living matter called ‘evolution’ was intended to prove what the origin was of the human species. In this letter to editor we present our opinion about the relationship between the xenotransplantation limitations and Charles Darwin theory on Human evolution.